عقود العمارة العربية - الإسلامية وأثرالعقد العباسي بالعمارة الغوطية في القرون الوسطى - ودح, هاني هاشم (Latakia University Journal -Engineering Sciences Series, 2019)
مع بداية القرن السابع الميلادي وتراجع الإمبراطورية البيزنطية ، بانت الحضارة العربية الإسلامية – بعلومها المختلفة - في الأفق واستفادت من سابقيها من العلوم وصقلتها وطورتها وقولبتها بقالبها الخاص فكانت المنهل الذي نهلت منه الإنسانية جمعاء . في هذا الوقت بالذات كانت أوربا تتخبط في غياهب الجهل والظلام والفساد ، وكان من الطبيعي أن تتجه إلى ذلك الينبوع الخصب بالعلم والمعرفة ، لتنـهل من مختلف علومه ( الطب، الكيمياء، البصريات، الفنون المعمارية، الزخرفية ، الرياضيات ...الخ ). والبحث الذي بين أيدينا يلقي الضوء على أثر صغير (القوس العباسي) من علم كبير (فنون العمارة العربية الاسلامية) بالعمارة الغوطية في أوربا. وذلك بعد تصنيف أقواس العمارة العربية – الإسلامية. ويهدف البحث إلى إيجاد ما يلي: 1. تصنيف عقود العمارة العربية - الإسلامية حسب العهود التي مرت بها. 2. أثر العقد العباسي على الطراز الغوطي من الناحيتين الإنشائية والفنية. With the decline of the Byzantine Empire at the beginning of the 7th century , the Arab –Islamic civilization – with its different branches of sciences – came to light . There can be no doubt that it had not only taken advantage of the sciences of former civilizations , but it had contributed to their refinement , development and molding . Therefore, it had been the source from which all humanity learned. Meanwhile, Europe was totally immersed in ignorance, darkness and corruption. Hence, it was quite normal to turn towards that rich source of science and knowledge to acquire and learn from its different sciences ( medicine, chemistry, optics, architecture, ornamentation, mathematics , etc ). This research casts light on a considerably small influence ( the Abbasid vault ) of the Arab – Islamic Architecture on the Gothic Architecture in Europe following the classification of the vaults of the Arab –Islamic Architecture. The research aims to find out the following : The classification of the vaults of the Arab –Islamic Architecture according to the eras they had been through. The influence of the Abbasid vault on the Gothic style from the structural and artistic angles.